Peran herding, overconfdence, dan endowment bias pada keputusan investasi investor pasar modal - Thea Diva Theressa; Rohmad Fuad Armansyah (Journal of Business & Banking, 2022)
Investment is one of the steps to get a financial advantage in the future. Investment decision-making involves thinking about action to make decisions. This study aims to examine the effect of Herding bias, Overconfidence bias, and Endowment bias on Investors' Investment Decision Making in the Capital Market. The sample consists of 150 respondents with the characteristics of being an active investor for at least 1 year in the capital market, having a minimum age of 17 years, and being Indonesian citizens. The sample  was taken by purposive sampling method through the distribution of electronic questionnaires to investors who have joined the capital market. The data were analed using Structural Equating Modeling (SEM) on Partial Least Square (PLS). The results of this study indicate that herding bias, overconfidence bias, and endowment bias affect investors' investment decision-making. The  partial test supports this results, showing a positive effect of each variable herding bias, overconfidence bias, and endowment bias on investment decision variables. This study has implications for investment decision makers with millennial demographics regarding financial bias behavior in the midst of information development, so it is important to base the fundamental and technical analysis on decision making.